Replication and Sensitivity Analysis of "Market Access and Quality Up-grading: Evidence from Four Field Experiments": A Comment on Bold et al. (2022b) - Ryan McWay; Karim Nchare; Pu Sun (Institute for Replication (I4R), 2023)
Bold et al. (2022b) investigate the effect of providing access to a larger, centralized market where quality is rewarded with a premium on farm productivity and framing incomes from smallholder maize farmers in western Uganda, using a series of randomized experiments and a difference-in-differences approach. We successfully reproduce the results of this study using the publicly provided replication packet. Then test the robustness of these results by re-defining treatment and outcome variables, testing for model misspecification and the leverage of outliers, and testing for non-random selection in the Fisher-permutation process. Our results show that the findings in Bold et al. (2022b) are robust to a variety of decisions in the research process. This evokes confidence in the internal validity of the findings.
Keywords: L14; L15; O13; Q12; Z00; 330; Reproducibility; Replication; Farm Productivity; Economic Development